Comparative Analysis of Two Different Techniques for Ridge Preservation Following Tooth Extraction: A Clinical and Radiographic Study - Naseemoon Shaik; Sai D. R. Rajoli; P. S. Sarika; Venkatesh Bejagam; Shifa F. Shajahan; Ghanta Snehika (Wolters Kluwer Medknow Publications, 2024)
Background: Ridge preservation following tooth extraction is essential for maintaining the alveolar bone structure and facilitating successful dental implant placement. Various techniques have been proposed for this purpose, but there remains a need for comparative analysis to determine their efficacy. Materials and Methods: This clinical and radiographic study compared two different techniques for ridge preservation: Technique A and Technique B. Fifty patients requiring tooth extraction were randomly assigned to either Technique A or Technique B group. Clinical parameters including pain, swelling, and soft tissue healing were evaluated postoperatively. Radiographic assessments were conducted to measure the dimensional changes in the alveolar ridge at baseline and after 3 months using cone-beam computed tomography (CBCT). Results: In the Technique A group, postoperative pain scores averaged 2.3 (±0.5) on a visual analog scale (VAS), while in the Technique B group, the average pain score was 2.5 (±0.6). The swelling was minimal in both groups with no significant difference. Soft tissue healing was satisfactory in both groups. Radiographically, the mean vertical bone loss was 1.2 mm (±0.3) in the Technique A group and 0.9 mm (±0.4) in the Technique B group, with a statistically significant difference (P < 0.05). Conclusion: Both Technique A and Technique B demonstrated favorable outcomes in terms of postoperative discomfort and soft tissue healing. However, Technique B showed superior preservation of vertical ridge dimensions compared to Technique A. Therefore, Technique B may be considered more effective for ridge preservation following tooth extraction.